The Peculiarities of The Organization of Military-Patriotic Education in Secondary Schools - Tilavoldiev Shakhobiddin; Khasanov Nurmukhammad (Research Parks Publishers, 2021)
This article deals with the upbringing of the younger generation in the spirit of patriotism, patriotism, moral and spiritual preparation of citizens for the defense of the Fatherland, skillful defense of the Fatherland in times of danger, the establishment and effectiveness of military training and military education. Goes